Pemberdayaan masyarakat Desa Lomaya melalui Pelatihan Pengolahan Bubuk Cabai sebagai strategi Hilirisasi Hortikultura - Kasim, Rahmiyati; Bakari, Yuliana (Universitas Negeri Gorontalo, 2025)
The community empowerment program in Lomaya Village was implemented through product downstreaming training, integrated within the thematic community service (KKN) State University od Gorontalo. The purpose of this training was to equip the residents of Lomaya Village with product downstreaming skills (processing diversification) based on chili commodities to increase the added value and household income. The training activities consisted of three sessions: a lecture session, a practical session on processing chili powder with various flavors and chili oil, and a final stage involving organoleptic testing of the produced products. This activity resulted in two chili-based processed products, namely chili powder in five flavor variants and chili oil with papaya sticks. The produced chili powder was packaged, labeled, and branded as GON-Cabe (Gorontalo Chili). The results of the organoleptic test showed that all panelists liked every product produced in terms of taste, color, texture, and aroma.